Factors Influencing Educational Motivation - Hilal, Shekiba (Journal of Social Sciences - Kabul University, 2020)
The factors influencing educational motivation are multifaceted and depend on students' social, political, cultural, cognitive, and emotional development. This study is a literature-based research that synthesizes scholars’ perspectives on the subject. The objective of this paper is to enhance teachers’ awareness of the key factors that contribute to increasing students’ educational motivation. This research highlights that understanding the causes of educational motivation is essential for empowering students to take initiative in their learning journey. When students recognize the importance of motivation, they become more committed to their education and strive for academic success. Additionally, this study emphasizes the broader significance of motivation in education.